2017
DOI: 10.1186/s12915-017-0453-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomere heterogeneity linked to metabolism and pluripotency state revealed by simultaneous analysis of telomere length and RNA-seq in the same human embryonic stem cell

Abstract: BackgroundTelomere length heterogeneity has been detected in various cell types, including stem cells and cancer cells. Cell heterogeneity in pluripotent stem cells, such as embryonic stem cells (ESCs), is of particular interest; however, the implication and mechanisms underlying the heterogeneity remain to be understood. Single-cell analysis technology has recently been developed and effectively employed to investigate cell heterogeneity. Yet, methods that can simultaneously measure telomere length and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Additionally, RV infection did not alter stemness-related expression signatures as indicated by the transcriptomic activity of the GO gene set telomere maintenance (Figure 1F). Telomere maintenance is active in stem cells, but gets deactivated in differentiated somatic cells [24].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, RV infection did not alter stemness-related expression signatures as indicated by the transcriptomic activity of the GO gene set telomere maintenance (Figure 1F). Telomere maintenance is active in stem cells, but gets deactivated in differentiated somatic cells [24].…”
Section: Resultsmentioning
confidence: 99%
“…WA26 and RuES2 human embryonic cells were routinely maintained in undifferentiated state in E8 medium (A1517001, Life technologies) on Matrigel (356230, BD Bioscience)-coated tissue culture plates with daily medium feeding and passaged every 3-4 days with 0.5 mM EDTA in phosphate buffered saline (PBS) with 10 μM Rocki (sc-281642A, Santa Cruz) for maintenance. Osteosarcoma cells (U2OS) (HTB96, ATCC), cervix adenocarcinoma cells (HeLa) (CCL-2, ATCC), and human embryonic fibroblast (HEF) cells (derived from an aborted fetus) [18,19] were cultured in high glucose Dulbecco's modified Eagle's media (DMEM) plus 10% fetal bovine serum (FBS) (SH30070.03, Hyclone) with 1% penicillin and streptomycin. Colon carcinoma cell line (HCT116) (CCL-247, ATCC) was cultured in RPMI1640 (11875085, Life technologies) plus 10% FBS and 1% penicillin and streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
“…Based on our single cell analysis, hESCs express CD133 at high levels [18]. To validate the high expression of CD133 in hESCs, we assessed CD133 expression by qPCR using two paired primers (different loci at the cDNA of PROM1) in six human cell lines, including two hESC lines (WA26 and RuES2), a colon adenocarcinoma cell line (HCT116), an osteosarcoma cell line (U2OS), a cervix adenocarcinoma cell line (HeLa), and a human embryonic fibroblast (HEF) cell line (Fig.…”
Section: Cd133 Expression Is Elevated In Hescsmentioning
confidence: 99%
“…Cells with longer telomeres may have higher pluripotency potential and be positively selected from a heterogeneous population. Singlecell telomere length analysis coupled with RNA sequencing (scT&R-seq) revealed that hESCs with short telomeres exhibited more characteristics associated with differentiated lineages, whereas those with longer telomeres better maintained pluripotency (Wang et al, 2017). Telomere length also plays an important role in stem cell differentiation.…”
Section: Telomeres In Pscsmentioning
confidence: 99%